1764. The Gut: A Veiled Reservoir for Multidrug-resistant Organisms (MDROs) Below the Tip of the Iceberg. (26th November 2018) - Shimasaki, Teppei; Rhee, Yoona; Yelin, Rachel D; Ariston, Michelle; Ollison, Stefanie; Fogg, Louis; Dangana, Thelma; Cisneros, Enrique Cornejo; Weinstein, Robert A; Lolans, Karen; Schoeny, Michael; Lin, Michael Y; et al.
Abstract: Background: Clinical culture results are sometimes used to estimate the burden of multidrug-resistant organisms (MDROs) in hospitals. The association between positive clinical culture results and prevalence of MDROs in the gut is incompletely understood. Methods: Rectal swab or stool samples were collected daily from adult medical intensive care unit (MICU) patients and cultured for target MDROs using selective media between January 2017 and January 2018 at Rush University Medical Center, a 676-bed tertiary-care center in Chicago. Resistance mechanisms were confirmed by phenotypic methods and/or polymerase chain reaction. Clinical culture results during MICU stay were extracted from the hospital information system. Target MDROs included vancomycin-resistant Enterococci (VRE), carbapenem-resistant Enterobacteriaceae (CRE), extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL), carbapenem-resistant Pseudomonas aeruginosa (CRPA) and carbapenem-resistant Acinetobacter baumannii (CRAB). Patients with either a study or clinical culture positive for a target MDRO were analyzed. Results: We collected 5, 086 study samples from 1, 661 unique admissions (1, 419 patients) and included here data from 413 unique admissions (397 patients) with completed microbiologic analysis. Median (IQR) patient age was 65 (51–75) years and length of MICU stay was 3 (3–4) days. A total of 156 (37.8%) patients had a target MDRO detected from a study sample at any point; 57 (36.5%) patients had >1 MDRO detected. Overall prevalence of these MDROs was found to be 22.5% VRE, 6.5% CRE, 19.8% ESBL, 4.4% CRPA, and 0.7% CRAB. New MDRO acquisition was observed in 58 (14.6%) patients (figure). Once a target MDRO was detected in a study sample, 82.2% of subsequent study samples were positive for that MDRO. Only 13 (5.8%) patients had a positive clinical culture for any target MDRO during their MICU stay (table). Conclusion: Clinical cultures capture only the tip of the resistance iceberg and alone are insufficient to guide MDRO-targeted prevention strategies. Universal infection prevention measures are an alternative that may be preferred in settings where overall prevalence of MDROs is moderate or high and patients may be colonized with >1 MDRO. Disclosures: All authors: No reported disclosures.